Assessing quality of care in oesophago‐gastric cancer surgery in Australia. Issue 4 (6th September 2016) - Burton, Paul R.; Ooi, Geraldine J.; Shaw, Kalai; Smith, Andrew I.; Brown, Wendy A.; Nottle, Peter D.
Abstract : Background: Outcomes of oesophago‐gastric cancer are poor and highly variable between centres. It is important that complex multimodal treatments are applied optimally. Low case volumes at Australian centres mean that the analysis of crude outcomes is an inadequate assessment of overall quality of care. Detailed analysis across a range of quality domains offers the opportunity to measure performance. Methods: We compared data from the UK National Oesophago‐gastric Cancer Audit 2010 with the prospective Alfred Hospital oesophago‐gastric cancer database. Results: There were 314 Alfred and 17 279 UK patients identified. The volume of patients assessed by the Alfred was equal to the second highest quartile in the UK trust (4–5 new cases per month). Case ascertainment was better, capturing 84% of all oesophago‐gastric cancer within the Alfred prospective audit ( P < 0.001). The use of staging CT and PET scans was more common among Alfred patients (99% versus 89%, P < 0.01 and 83.8% versus 17%, P < 0.01, respectively). More patients embarked on a curative pathway ( P < 0.01), with greater use of neo‐adjuvant therapies. Acceptable lymph node yields were less in oesophagectomies (88.2% versus 96.2%, P < 0.01) and similar in gastrectomies (77.4% versus 74.6%, P = 0.61). Higher overall complications were observed in Alfred patients ( P < 0.01), predominantly due to respiratory complications. Perioperative mortality after resection and 1‐year survival was similar. Conclusions: Comparing a range of quality domains as a means of identifying areas of deficiency is feasible. This allows for contemporaneous improvements in service quality and may be more appropriate in the Australian setting than focusing on volume.